Systematic review and meta-analysis of postcarotid endarterectomy hypertension after eversion versus conventional carotid endarterectomy - Demirel, Serdar; Goossen, Käthe; Probst, Pascal; Böckler, Dittmar (Journal of vascular surgery, 2017)
Objective: Blood pressure (BP) instability after carotid endarterectomy (CEA) is a risk factor for cerebrovascular and cardiovascular complications. The role of the operative technique in the development of post-CEA hemodynamic instability is unclear. The primary goal of this study was to systematically review the literature to determine whether hypertension in the early postoperative period is dependent on the surgical technique used. Methods: We searched MEDLINE, Cochrane CENTRAL, and Web of Science through June 2016 without restrictions to language or starting date. The interventions of interest were eversion CEA (E-CEA) compared with conventional CEA (C-CEA) with or without patch plasty. The primary outcome of interest was the incidence of postoperative need for vasodilator therapy because of hypertension in the early postoperative period, the duration of which was predeﬁned in the individual studies. Secondary outcomes were the intergroup mean difference of the mean within-group changes of postoperative (24 hours) to baseline systolic BP, the incidence of hypotension requiring vasopressor therapy, and the rate of complications. The odds ratio (OR) of each binary outcome was pooled across studies with its 95% conﬁdence interval (CI). For meta-analysis of continuous outcomes, the weighted mean differences with the corresponding 95% CIs were pooled. Strength of evidence of the outcomes was judged according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) guidelines.Results: We identiﬁed six studies, of which four were nonrandomized prospective and two retrospective with low to moderate risk of bias. In addition, results of a post hoc analyses of a randomized controlled trial were included, resulting in a total number of seven included studies. Duration of the postoperative study period ranged from 1 to 6 days. The meta-analysis of all studies regarding the primary outcome demonstrated increased rates of post-CEA hypertension after E-CEA (pooled OR, 2.75; 95% CI, 1.82-4.16; I2 ¼ 49.9%). The pooled weighted intergroup mean difference between the E-CEA and C-CEA effects on postoperative systolic BP was þ12.92 mm Hg (95% CI, 8.06-17.78; I2 ¼ 93.6%; P < .0001). Hypotension was signiﬁcantly higher in the C-CEA group (pooled OR, 11.37; 95% CI, 1.95-66.46; I2 ¼ 0%). There was no difference in postoperative complications including myocardial infarction, stroke, neck hematoma, or death. Strength of evidence contributing to the primary outcome as well as the hypotension outcome was graded as moderate and that contributing to the other secondary outcomes was graded as very low.Conclusions: E-CEA increases the risk for post-CEA hypertension, whereas C-CEA is more often associated with hypotension, Careful BP monitoring at least in the early postoperative period after CEA is andatory, especially when the eversion technique is used. (J Vasc Surg 2017;65:868-82.)